Предмет: Алгебра,
автор: xxxlokxxx
Помогите пожалуйста!!! Срочно надо!
Приложения:
Ответы
Автор ответа:
2
если х = у + z, то:
х(уz + 1) - у(хz + 1) - z(ху + 1) =
= (у + z)(уz + 1) - у(z(у + z) + 1) - z(у(у + z) + 1) =
= у²z + у + уz² + z - у²z - уz² - у - у²z - уz² - z =
= - у²z - уz² = -уz*(у + z) = -уz * х = -хуz
Похожие вопросы
Предмет: Математика,
автор: Farretug
Предмет: Английский язык,
автор: klubromanti20
Предмет: Қазақ тiлi,
автор: omirbekalmas2011
Предмет: Биология,
автор: Alexandro2015
Предмет: Математика,
автор: Zheka0406